Sistem Pendukung Keputusan Berbasis Web untuk Menentukan Penjurusan (IPA/IPS/Bahasa) pada SMA Islam Bumiayu - Tresna Yudha Prawira; Dimara Kusuma Hakim (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2011)
The instances of secondary school (HIGH SCHOOL) in determining the direction to grade X which will be purposed requires a lot of consideration. As for the consideration of the determination for the students who will be leadd many factors to predestination, suppose that is taken from the marks of the semester, the test of academic potential and selection of students. The percentage of the three marks can be calculated and taken the final result to determine IPA, IPS or language on each of their students. Decision making is the perfect solution, because it is the right decision can give you the best results. As for the purpose of this research can be applied, namely: a decision support system to determine in addition the IPA, IPS or language at HIGH SCHOOL. The results of this research in the form of a decision support system (DSS) to determine in addition the IPA, IPS or language at HIGH SCHOOL